ÙØ¹Ø§Ù„ÙŠØ© ÙÙŠØ¯ÙŠÙˆ ÙƒØ§Ù†ÙØ§ (canva)ÙÙŠ ØªØ±Ù‚ÙŠØ© Ø¥ØªÙ‚Ø§Ù† Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Laili Qurotu Ain; Ruwaida Hudatullah; Adi Rimbun Kusuma Negara (Lughatu Ad-dhat, 2022)
This study aims to test the effectiveness of video (Canva) in improving the mastery of Arabic vocabulary for eighth-grade students in the Middle School of Muslim Education in Dasan Malang. In order to increase vocabulary mastery and provide new colors in learning Arabic vocabulary. The research method uses quantitative analysis. The type of research used is an experimental research by dividing two classes into two groups, the experimental group and the control group that were chosen randomly, then given a pre-test to determine whether there is a difference between the experimental and control groups, and then looking for the effect of treatment through the post test on both groups. The researcher collects the data and then simplifies all the collected data, presents them in an organized order, and then processes the data using the SPSS ver application program. 25 for windows. The data analysis used descriptive statistical analysis, and this study was applied to a sample of 60 students from the Muslim Education School in Dasan Malang. Data collection using research tools in the form of: (1) test (2) tests (3) documentation. The results showed that after performing the pre- and post-test, the results of the independent sample t-test for the experimental group (VIII) were obtained with a census value of 5.279 > 1.671. H0 was rejected and Ha accepted, and it can be concluded that the video (Canva) can improve the mastery of Arabic vocabulary.